Qualitative examination of the perceived effects of a comprehensive smoke-free law according to neighborhood socioeconomic status in a large city - Ignacio de Loyola González-Salgado, M.A.; Jesús Rivera-Navarro, PhD; Xisca Sureda, PhD; Manuel Franco, MD PhD (SSM: Population Health, 2020)
Smoke-free legislations aim to protect non-smokers from second-hand smoke (SHS) exposure and improve population health outcomes. The aim of this study was to explore residents’ perceptions to understand how people living in distinctive SES neighborhoods are differently affected by comprehensive smoke-free laws in a large city like Madrid, Spain.We conducted a qualitative project with 37 semi-structured interviews and 29 focus group discussions in three different SES neighborhoods within the city of Madrid. Constructivist grounded theory was used to analyze the transcripts.One core category arose in our analyses: Neighborhood inequalities in second-hand smoke (SHS) exposure in outdoor places. The enactment of the comprehensive smoke-free law resulted in unintended consequences that affected neighborhoods differently: relocation of smokers to outdoor setting, SHS exposure, noise disturbance and cigarette butt littering. Changes in the urban environment in the three neighborhoods resulted in the denormalization of smoking in outdoor public places, which was more clearly perceived in the high SES neighborhood. Changes in the built environment in outdoor areas of hospitality venues were reported to actually facilitate smoking. Comprehensive smoke-free laws resulted in denormalization of smoking, which might be effective in reducing SHS exposure. Extending smoking bans to outdoor areas like bus stops and hospitality venues is warranted and should include a public health inequalities perspective.